PENGARUH UNSUR SILIKON PADA ALUMINIUM ALLOY (Al – Si) TERHADAP SIFAT MEKANIS DAN STRUKTUR MIKRO - Ratih Ponco K.S; Erwin Siahaan; Steven Darmawan (Program Studi Teknik Mesin Universitas Tarumanagara, 2017)
Abstract: PENGARUH UNSUR SILIKON PADA ALUMINIUM ALLOY (Al – Si) TERHADAP SIFAT MEKANIS DAN STRUKTUR MIKRO Ratih Ponco K.S., Erwin Siahaan dan Steven Darmawan Jurusan Teknik Mesin, Fakultas Teknik Universitas Tarumanagara Aluminum is one of type in material non-ferrous metals are frequently and widely used in fields of application in industry. One application that performed in the industrial world, namely Aluminum Silicon (AlSi) which are used for the motor piston components. To get better mechanical properties then the integration of Aluminum Silicon research done by arranging the variety of Si element content on a percentage of 6, 8, and 10% Si.Testing is done by using a blend of 10% genuine with further lowering the Si content to reach 6% and 8% by adding pure aluminum. The test showed that the level of harness decreased 12,5% and also the ability of toughness decreased by 4%. Observation show that the microstructure is relatively homogeneous and there is a dominant form of micro-structure of pure Al and several dendrites CuAl.